A study of factors influencing generation Y’s purchase intention on luxury brand in Malaysia - Lim, Jiang Yi (2018)
This study aimed to examine the factors influencing the Generation Y’s purchase intention on the luxury brand. Purchase intention always be developed and affected by different reasons that what makes the Generation Y that plan to purchase the luxury brand or product in the future. In this research study, our target population will be the Generation Y among Malaysia. We conducted a total of 200 sets of the questionnaire to our target population by using the convenience sampling technique. In order to assess the reliability, the Cronbach’s alpha will be used to measure the reliability test. Moreover, the data collected will be analyzed by using the Perason’s Correlation and Multiple Regression Analysis. Therefore, based on the results of the research study, the independent variables are perceived quality, celebrity endorsement, social status, social influence and brand trust will be consider as the determinants of the factors influence the purchase intention towards the luxury brand.